Comparative outcomes for older adults undergoing surgery for bladder and bowel dysfunction. Issue 8 (5th April 2021) - Suskind, Anne M.; Zhao, Shoujun; Nik‐Ahd, Farnoosh; Boscardin, W. John; Covinsky, Kenneth; Finlayson, Emily
Abstract: Background/Objectives: To compare surgical outcomes between vulnerable nursing home (NH) residents and matched community‐dwelling older adults undergoing surgery for bladder and bowel dysfunction. Design: Retrospective cohort study. Participants: A total of 55, 389 NH residents and propensity matched (based on procedure, age, sex, race, comorbidity, and year) community‐dwelling older adults undergoing surgery for bladder and bowel dysfunction [female pelvic surgery, transurethral resection of the prostate, suprapubic tube placement, hemorrhoid surgery, rectal prolapse surgery]. Individuals were identified using Medicare claims and the Minimum Data Set (MDS) for NH residents between 2014 and 2016. Measurements: Thirty‐day complications, 1‐year mortality, and weighted changes in healthcare resource utilization (hospital admissions, emergency room visits, office visits) in the year before and after surgery. Results: NH residents demonstrated statistically significant increased risk of 30‐day complications [60.1% v. 47.2%; RR 1.3 (95% CI 1.3–1.3)] and 1‐year mortality [28.9% vs. 21.3%; RR 1.4 (95% CI 1.3–1.4)], compared to community‐dwelling older adults. NH residents also demonstrated decreased healthcare resource utilization, compared to community‐dwelling older adults, changing from 3.9 to 1.9 (vs.1.1 to 1.0) hospital admissions, 11 to 10.1 (vs. 9 to 9.7) office visits, and 3.4 to 2.2 (vs. 1.9 to 1.9) emergency room visits from the year before to after surgery. Conclusion: Despite matching on several important clinical characteristics, NH residents demonstrated increased rates of 30‐day complications and 1‐year mortality after surgery for bowel and bladder dysfunction, while demonstrating decreased healthcare resource utilization. These mixed findings suggest that outcomes may be more varied among vulnerable older adults and warrant further investigation.